1989
DOI: 10.1097/00004032-198905000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of the Injurious Effects of Q-switched Nd:YAG Lasers and Their Outdoor Applications

et al.

Abstract: Comparison of the dose-response relationship of retinal damage induced by Q-switched (Q-sw) Nd:YAG lasers was conducted for rabbits and monkeys. Experimental results indicated that the two probit regression lines were parallel to each other, and the damage threshold (ED50) ratio was approximately 1:3.57. Observations of the injurious effects of Q-sw Nd:YAG rangefinders--the total energy level being about 10-100 mJ--and their injurious distances are reported in this paper. A brief description is given of coagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This corresponds to the volume 565.49 mm 3 for monkey and 1140.40 mm 3 for rabbit. Jiemin et al 51 reported ED 50 values for both monkey and rabbit as 4.32 and 1.21 mJ cm À2 using a Nd:YAG having a 5 ns laser pulse. In the present work, we report the ED 50 values calculated for the four laser wavelengths considering the shape of the melanosome as hexagonal and cylindrical.…”
Section: Resultsmentioning
confidence: 99%
“…This corresponds to the volume 565.49 mm 3 for monkey and 1140.40 mm 3 for rabbit. Jiemin et al 51 reported ED 50 values for both monkey and rabbit as 4.32 and 1.21 mJ cm À2 using a Nd:YAG having a 5 ns laser pulse. In the present work, we report the ED 50 values calculated for the four laser wavelengths considering the shape of the melanosome as hexagonal and cylindrical.…”
Section: Resultsmentioning
confidence: 99%